Implementation of 3D IoT Mapping Tourism in Identifying Green Tourism Potential - Hasibuan, Annalisa Sonaria; Chan, Andi Supriadi; Destiadi, Rezha; Husna, Meryatul (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Tourism is a key sector in Indonesia's economic development, contributing significantly to national growth. With a target of generating USD 30 billion in foreign exchange and attracting 22.3 million international tourists by 2024, the sector aligns with the 2020-2024 RPJMN narrative to strengthen economic resilience. Emphasizing sustainable and green tourism, Indonesia promotes eco-green principles to reduce environmental impacts, conserve natural and cultural heritage, and empower local communities. The study highlights the use of Internet of Things (IoT) and 3D mapping technologies to enhance tourism management and promotion, focusing on Lingga Village in Karo Regency, North Sumatra. These innovations aim to present spatial data interactively, improving accessibility and tourist experiences. Survey results show that 85.4% of respondents strongly support the use of 3D modeling for tourism promotion and education. Despite its potential, challenges such as limited budgets, small sample sizes, and community engagement remain obstacles. This research underlines the importance of integrating green tourism, technology, and sustainable practices to achieve equitable regional growth and environmental conservation in Indonesia.